48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-1061
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Boundary-Layer Transition Experiments in a Mach-6 Quiet Tunnel

Abstract: The Boeing/AFOSR Mach-6 Quiet Tunnel has achieved quiet flow to stagnation pressures of 146 psia, and intermittently quiet flow between 146 and 169 psia. In an attempt to measure natural transition under quiet flow, a 3-m-circular-arc compression cone was tested with a nearly sharp nosetip. Using temperature-sensitive paint, hot streaks were observed to develop near the rear of the cone at high pressures under quiet flow. The streaks do not appear under noisy flow. The cause of the hot streaks remains unknown,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
6
29
0
Order By: Relevance
“…These streaks look similar to the streamwise streaks observed in the Purdue experiments using temperature sensitive paint (Berridge et al, 2010). The qualitative similarity of the "hot" streaks observed in our simulations and the streamwise streaks …”
Section: Fundamental Breakdownsupporting
confidence: 84%
See 2 more Smart Citations
“…These streaks look similar to the streamwise streaks observed in the Purdue experiments using temperature sensitive paint (Berridge et al, 2010). The qualitative similarity of the "hot" streaks observed in our simulations and the streamwise streaks …”
Section: Fundamental Breakdownsupporting
confidence: 84%
“…Figure 5.14: Time-averaged skin friction from CFUND 1 (top), CFUND 2 (center) and CFUND 3 (bottom). The streamwise alligned "hot" streaks observed in our simulations looks qualitatively similar to the streamwise streaks observed in the Purdue experiments using temperature sensitive paints for a flared cone (Berridge et al, 2010). The time-and azimuthally-averaged streamwise velocity profiles plotted in wall coordinates can provide more insight on how far transition has progressed.…”
Section: Fundamental Breakdownsupporting
confidence: 79%
See 1 more Smart Citation
“…The flow parameters chosen are those of the experiments by Schneider and coworkers 5,6 in the Boeing/AFOSR Mach 6 quiet-flow Ludwieg Tube at Purdue University. The approach flow has a Mach number of 6 and a unit Reynolds number of 9.276 x 10 6 m −1 .…”
Section: Physical Problem and Computational Methodsmentioning
confidence: 99%
“…It is uncertain how pressure is transmitted to the sensing element through this epoxy, so the active sensing area is unknown. It has been stated earlier that the sensing element size was 1 × 1.6 mm, [18][19][20][21][22] but further communication with the sensor manufacturer revealed that to be an error.…”
Section: B Model and Instrumentationmentioning
confidence: 99%